Introducing Traditional Games in Elementary School Physical Education Learning - Widodo, Haryo Mukti (Journal of Sport Moovera (JSM), 2023)
Traditional games need to be introduced from an early age in order to preserve and develop culture. Activities that aim to provide knowledge related to traditional games so that students can continue to preserve cultural heritage, so that students have character and have a national spirit. The results obtained from the activities carried out by students are more familiar with traditional regional games and are able to practice them well. With this socialization, it is expected that students can do more physical activity so that the health and social status of students will increase. Students are also expected to be able to maintain cultural heritage so that it is well maintained and increase self-confidence to become the nation’s successor with character.